KEMAMPUAN MEMBACA ARAB MELAYU MAHASISWA ANGKATAN 2021 PROGRAM STUDI PENDIDIKAN BAHASA INGGRIS FKIP UNIVERSITAS RIAU - Ihwani Pangesa; Imayana, Imayana; Meilani Fatzuarni; Hasnah Faizah AR (PUSTAKA: Jurnal Bahasa dan Pendidikan, 2023)
This research is more focused on the ability to read words in Arabic-Malay script which is now a lack of attention and ability of students in learning Arabic-Malay which is only carried out once in today's lecture subjects, so the authors are motivated to research this Arabic-Malay reading ability. The problem in this research is about how the ability to read and how far the skills in Arabic-Malay are in class C class C students of the English Language Education Study Program, FKIP, University of Riau. The method used by the researchers in this research is a quantitative method that is descriptive in nature with a research sample of 39 students from class C of 2021, who are now taking semester III of the 2022/2023 Academic year. The purpose of this study is to describe the ability to read Arabic-Malay class 2021 class C English Language Education Study Program, FKIP University of Riau. In this study, researchers used data collection techniques, namely the test technique through the G-form which was distributed to students. The data analysis technique used by researchers in this study is to collect test results, provide an assessment in the form of a score, look for the percentage of results in reading achievement, and calculate the average score.